2020
DOI: 10.4236/aim.2020.109035
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Efficacy of <i>Withania somnifera</i> (Ashwagandha) against Hepatitis C Virus Activity: <i>In Vitro</i> and <i>in Silico</i> Study

Abstract: Objective: Evaluation antiviral effects of Withania somnifera (Ashwagandha) leaf extract against HCV. Methods: cell proliferation was assessed using MTT assay after isolation of lymphocyte cells and treated with Ashwagandha water extract (ASH-WX) (6.25 mg/ml-100 mg/ml). Assessment of quantitative Real-time PCR, Colony forming assay, TNF-α and molecular docking studies after infection of normal lymphocyte cells with 1 ml (1.5 × 10 6 HCV) serum then incubated with ASH-WX at concentration 25 mg/ml & 50 mg/ml. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The viral load reduction as measured by PCR was noted as 6.241 × 103 IU/mL at 25mg/ml concentration. [21] A study on Glycyrrhizin, a major component of Yashtimadhu,…”
Section: Discussionmentioning
confidence: 99%
“…The viral load reduction as measured by PCR was noted as 6.241 × 103 IU/mL at 25mg/ml concentration. [21] A study on Glycyrrhizin, a major component of Yashtimadhu,…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it might be a promising option for managing SARS-CoV-2 either as a preventive, a primary symptomatic treatment, or a substitute medication (Mofed et al, 2020).…”
Section: Withania Somnifera: Therapeutically Potential Activitiesmentioning
confidence: 99%
“…Several studies have shown the hepatoprotective activity of this plant without toxicity [ 127 , 128 ]. Withaferin A performs a crucial function as antiviral agents against several viruses, including HIV-1 [ 129 ], HPV [ 130 ], HSV [ 131 ], and infectious bursal diseases virus (IBDV) [ 131 ]. In a recent study, it has been reported that withaferin-A and withanone could bind and stably interact with the catalytic site of TMPRSS2, suggesting their use in the blocking of COVID-19 viral entry into host cells [ 132 ].…”
Section: Hepatoprotective Agentsmentioning
confidence: 99%